The (misleading) role of animal models in drug development - Hartung, Thomas (Frontiers in Drug Discovery, 2024)
Animals like mice and rats have long been used in medical research to help understand disease and test poten3al new treatments before human trials. However, while animal studies have contributed to important advances, relying too heavily on animal models can also mislead drug development. This ar3cle explains for a general audience how animal research is used to develop new medicines, its benefits and limita3ons, and how more accurate and human and humane techniques, aka alterna3ves to animal tes3ng, could improve this process.